ETHICAL FORM OF SOLVING ENVIRONMENTAL PROBLEMS AS ENSURING SECURITY OF SOCIETY IN CONDITIONS OF GLOBALIZATION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This work analyzes the dialectics of the interdependence of the economy and theethics of the organization of labor and moral principles and norms of the attitude of social groupsof society to the problems of ecology, in various forms of its manifestation. We are talking, firstof all, about such varieties of ecology, considered through the prism of economic processes, suchas social ecology, environmental ethics and bioethics, affecting the natural, biological and sociallevels and forms of development of the material world (matter). From the perspective of this study,the author examines the specificity and difference in the manifestation, in market relations, of theorganization of labor, on the one hand, and the influence of the economy on work ethics, considered through the prism of the impact of production on the ecological state of the environment andits inhabitants, from among the flora and fauna , and the person himself (society) in states, differingin the level of their economic development, on the other hand.In this regard, in the context of solving the problems of the correlation and mutual influenceof the economy and the environment in the context of globalization, an analysis is given of thedifferences in the formation and development of capitalism, as a socio-political system, relativelydeveloped, post-information, and developing, raw-material-dependent countries of the world.
Keywords: economics, capitalism, ecology, ethics, social ecology, humanitarian ecology, bioethics, environmental ethics, work ethics, nature, ecosystem.